Droga do Emaus drogą ku wierze w zmartwychwstanie - Mielcarek, Krzysztof (Verbum Vitae, 2009)
The article proposes a narrative approach toward a pericope of Luke 24,13-35. By singling out three main criteria of time, space and characters the author builds a picture of a story in which Luke tells his fellow-believers about reality of Jesus’ resurrection. His narrative does not function as a definite prove of the fact of resurrection, but is thought as a kind of encouragement for Christians to meet with living and resurrected Jesus Christ truly present in the rite of breaking bread.